Plasmatic biochemical variables associated with polymorphisms in the endothelin-1 and endothelin-1 receptor a genes in hypertensive patients : pilot study - Lassen, Oscar (2016)
Fil: Lassen, Oscar. Hospital Córdoba. Centro de Chagas e Hipertensión. Departamento de Semiología; Argentina.